Efeito de fungicidas protetores e sistêmicos e molibdênio, na emergência, produção e fixação simbiótica do nitrogênio em soja (Glycine max (L) Merril) - Zambolim , Laércio; Sigueyuki Sediyama , Carlos; Ribeiro , Antônio Carlos; Martins Chaves , Geraldo (Revista Ceres, 2025)
This study was carried out in Viçosa and Ponte Nova, State of Minas Gerais, to evaluate the effects of treating ’Santa Rosa’ soybean seeds with a slurry of fungicides and molybdenum oxide (Mo03, 13g/ha). Emergence, grain yield and nodulation were then analyzed after inoculation with 0.4% Rhizobium japonicum. The fungi Colletotrichum truncatum and Cercospora kikuchii were also detected on the seeds prior to planting.